Climatic behaviour of solar photovoltaic integrated with phase change material. (15th June 2018) - Khanna, Sourav; Reddy, K.S.; Mallick, Tapas K.
Highlights: Climates with less variations in ambient temperature are more suitable for PV-PCM. Cold climates are less suitable for heat extraction by PCM from PV. PCM integration with PV performs better in climates having low wind speed. PV cooling using PCM is more effective for climate with wind flow across the system. Climates having high solar radiation are better for PCM systems. Abstract: In photovoltaic (PV) cells, a large portion of the solar-irradiance becomes heat which shoots the cell temperature up and decreases its electrical efficiency. The heat can be removed using phase-change-material (PCM) at the rear of the PV. In literature, the researchers have reported the performance of PV-PCM for their respective locations. However, selection criteria for climates suitable for PCM integration are not reported yet. Thus, it has been carried out in the current work. The model has been validated against the experimental measurements. It has been concluded that (i) the climates having less variations in the ambient temperature are more suitable for PCM integration. The electricity enhancement achieved by PV cooling is 9.7%. It reduces to 6.6% for the climate having large variations, (ii) Heat extraction by PCM-systems is more effective in warm climates in comparison to cold climates, (iii) PCM integration performs better in climates with low wind-speed, (iv) PCM is more effective for the climates where wind-flow is across the PV and (v) Climates having high solar-radiation is better for heat removal by PCM.